Automatic Rebar Bending Machine to Form Rectangular Stirrups - Yaghmour, Bahaa; Qwasmh, Sajed; Abuafifeh, Iyad (Palestine Polytechnic University (PPU) - mechatronics, 2018)
This project considers design and building an automatic rebar bending machine to form stirrups with different dimensions and sizes. The machine is proposed to be accurate and precise with fast production rate, also it must be safe and easy to program and operate. The machine aims to form closed loop stirrups fromsteelrebarswhich used in concrete beams and columns specially for 8mm steel bars without needs human assist, this done by entering the appropriate dimensions of stirrups by the user via Human Machine Interface (HMI) then automatically the machine inserts the bar then bend it to the required stirrup dimensions based on the algorithm build in Programing Logic Controller (PLC). إن الهدف الاساسي و المرجو من هذا المشروع هو تصميم و بناء ماكنة تقوم بثني قضبان حديد التسليح أتوماتيكاً لتشكيل الكانات بمختلف أبعادها وأحجامها ,هذه الماكنة اقترحت لكي تكون عملية الإنتاج سريعة و أكثر دقة , بالإضافة إلى ذلك أن تكون آمنة و تكون برمجتها و عملية التعامل معها سهلة. الماكتة تقوم بثي قضبان حديد التسليح اللتي يكون قطرها 8 ملم لتشكيل كانات مستطيلة الشكل والتي تستخدم في الأعمدة والجسور الإسمنتية المسلحة دون الحاجة للقوى البشرية في عملية التشكيل. تتم العملية من خلال عدة خطوات يتم التحكم بها عن طريق المتحكم المنطقي المبرمج المرتبط بالماكنة, حيث يقوم المستخدم للماكنة بإدخال أبعاد الكانة المراد تشكيلها عن طريق شاشة تحكم تفاعلية مرتبطة مع المتحكم ومن ثم تقوم الماكنة بإدخال القضبان و تنتهي بتشكيلها حسب الابعاد المطلوبة.
CD, no of pages 107, 5/2018 ميكاترونيكس, in the store
Keywords: Automatic ,Rebar Bending ,Machine to Form ,Rectangular Stirrups